Copper complexes with new oxaaza-pendant-armed macrocyclic ligands: X-ray crystal structure of a macrocyclic copper(II) complex - Vicente, Manuel (2005)
The synthesis of new oxaaza macrocyclic ligands (2-4) derived from O1,O7-bis(2-formylphenyl)-1,4,7-trioxaheptane and functionalized tris(2-aminoethyl)amine are described. Mononuclear copper(II) complexes were isolated in the reaction of the corresponding macrocyclic ligand and copper(II) perchlorate. The structure of the [Cu(2)](ClO4)2 complex was determined by X-ray diffraction analysis. The copper(II) ion is five-coordinated by all N5 donor atoms, efficiently encapsulated by the amine terminal pendant-arm, with a trigonal-bipyramidal geometry. The complexes are further characterized by UV-Vis, IR and EPR studies. The electronic reflectance spectra evidence that the coordination geometry for the Cu(II) complexes is trigonal-bipyramidal with the ligands 1 and 2 or distorted square-pyramidal with the ligands 3 and 4. The electronic spectra in MeCN solutions are different from those in the solid state, which suggest that some structural modification may occur in solution. The EPR spectrum of powder samples of the copper complex with 2 presents axial symmetry with hyperfine split at g// with the copper nuclei (I = 3/2), which is characteristic of weakly exchange coupled extended systems. The EPR parameters (g// = 2.230, A// = 156 × 10-4 cm-1 and g[perpendicular] = 2.085) indicate a dx2-y2 ground state. The EPR spectra of the complexes with ligands 3and 4 show EPR spectra with a poorly resolved hyperfine structure at g//. In contrast, the complex with ligand 2 shows no hyperfine split and a line shape which was simulated assuming rhombic g-tensor (g1 = 2.030, g2 = 2.115 and g3 = 2.190).